Ecological and economic profile of cities: on the way to sustainable development - V. Nazarenko; О. Voytovich (Zemleustrìj, Kadastr ì Monìtorìng Zemelʹ, 2024)
Ecology has become an urgent global problem for modern metropolises. Cities seek to balance their economic growth and preserve the state of the environment. One of the programs that more and more cities are implementing at the municipal level is the sustainable development program (based on the Paris Climate Agreement). This study presents cities' environmental and economic profiles through the prism of their economy. The main focus of the work is on waste management, reducing harmful emissions, and increasing the economic development of cities. The principles of integration of a modern green city were worked out and analyzed to determine the optimal strategies for its development. Such a strategy should synchronize the economic activities of the city with the goals of the sustainable development program.